Sustainability Performance and Corporate Financial Performance: The Moderating Effect Of Corporate Governance - Anita; Fatmasari, Agustini (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - This research intends to interpret corporate governance's effect on the relationship between sustainability performance and financial performance. Research Method - The research method used is panel data regression. Research data is quantitative data obtained from the Indonesian Stock Exchange. The sample selection procedure used a purposive sampling method from 767 listed companies, and 53 met the criteria. Findings - The research results prove that board size and CEO duality do not affect sustainability performance. The board independence and female directors significantly impact sustainability performance. Furthermore, researchers also found that corporate governance cannot moderate the relationship between sustainability and financial performance. Implication - The research findings conclude that board independence and female directors can pay more attention to sustainability performance, which can be used as a reference in making corporate governance and sustainability policies.